Optimization of PKK Anawoi Village in Increasing Digital Literacy and Coastal Tourism-Based Creative Industries: Optimalisasi PKK Kelurahan Anawoi dalam Meningkatkan Literasi Digital dan Industri Kreatif Berbasis Pariwisata Pesisir - Sarmadan, Sarmadan; Sakti, La Ode Awal; Sutoyo, Muhammad Nurtanzis; Baharuddin, Zubair; Saputra, Nanda (Universitas Lancang Kuning, 2025)
Kampoh Malasso – Kampung Bajo Anaiwoi is a floating village located in Anaiwoi Village, Tanggetada District, Kolaka Regency, Southeast Sulawesi Province. The majority of people in this floating village live by utilizing marine products, but limitations in business management and product marketing are the main obstacles in improving their standard of living. Seeing this condition, the USN Kolaka Community Partnership Program (PKM) Team tried to collaborate with the Anaiwoi Village PKK Team to help the local community through training and mentoring that focuses on aspects of management, product packaging, and digital marketing in order to increase literacy, development of MSMEs and creative industries based on coastal tourism. The PKM implementation method is divided into 5 stages, namely: socialization, training, application of technology, mentoring and evaluation, and program sustainability. This service resulted in several important achievements related to the level of empowerment of PKK partners in Anaiwoi Village, namely: 1) Increasing Managerial Knowledge: Training participants succeeded in improving their managerial skills, especially in preparing plans and managing PKK programs; 2) Improving Packaging Skills, where partners are skilled in packaging marine products and MSMEs, such as packaging for Malasso Dried Fish, Anaiwoi Green Banana, SaPa Ongol-Ongol (Coconut Sago), Fresh Smoothies, Malasso Village Krips (Cassava Chips), as well as digital printing creative industries (shirt screen printing, etc.); and 3) Improving Digital Marketing Skills: Partners are able to utilize digital technology to market their products more widely through websites and social media, as well as improve their skills in creating promotional content that has an impact on strengthening literacy at the same time.